Cerebral venous thrombosis and COVID-19: A silent killer during the pandemic? - Gutiérrez-Zevallos, Juan Diego (2021)
Cerebral venous thrombosis (CVT) is a rare clinical condition that consists of an obstruction of the dural venous sinuses or the cerebral cortical veins, triggering intracranial hypertension and symptoms such as headache, seizures and coma among others. CVT has recently been associated as a neurological complication of the Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2). Objective: To describe reported cases of CVT in patients with Coronavirus Disease 2019 (COVID - 19). Material and Methods: A literature search was conducted on PubMed to collect only case reports of patients with COVID-19 who developed CVT. Results: Report of 13 patients were analyzed and information was collected about sex, age, comorbidities, severity of COVID-19, type of CVT, treatments received, complications and the final outcome. Conclusion: CVT associated with COVID-19 can occur in patients with varied characteristics, often with serious complications and in some cases, a fatal outcome.